Identity and Muslim Solidarity in French Literature: A Sociological Study of Qu’Allah Bénisse La France by Abd Al Malik - sunahrowi sunahrowi (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
This study aims to examine Islam sociologically with the point of view of Durkheim about mechanical and organic solidarity, race, religion and morality. Mechanical solidarity arises because of the similarity of fate, conditions, and challenges encountered. Race and religion are a reinforcement that binds between their fellow mothers while morality is related to beliefs, and sentiment from the majority, as well as the ability to survive in the midst of French social life. Islam in France is an interesting factor to study, not only related to the facts as the second largest religion (8-9 %) but also about the conditions faced by Muslims there. Literary works provide other alternatives to see the social reality. Qu ‘Allah Bénisse La France gave a picture of the struggle of minorities and immigrants in France. They are faced with the challenges of identity and at the same time differences in identity. One side, they must carry out their obligations as a Muslim and the other, they must adapt to different social norms and life. This study chose the theoretical approach in the form of material and non-material concepts. Data in this study is in the form of words and sentences related to research topics.